Slack resources and innovation in Vietnamese SMEs: A behavioural, stewardship, and institutional perspective - Tam Thanh Nguyen; Chieu Duc Trinh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Slack resources are usually identified as an endogenous motivation for firms' innovation. Still, it is crucial to assess the importance of slack in supporting innovation, especially in different institutional contexts. Therefore, the paper investigates the relationship by exploring a longitudinal dataset of 15,589 observations from about 2,500 surveyed manufacturing small and medium enterprises (SMEs) in Viet Nam. The analysis reveals that slack resources promote innovation in different ways. While the financial slack harms the efforts of introducing innovation, the presence of human resource slack encourages firms to engage more in innovation activities resulting in the introduction of new products or business processes. We further found that for firms located in a more favourable business environment the impact of human resource slack on innovation is less pronounced whereas the negative impact of financial slack is lessened. The above results enrich the current literature on the relationship between slack and innovation within an institutional context in emerging economies.
Keywords: O30; D02; D21; 330; innovation; slack; stewardship theory; behavioural theory; institutional economics theory; emerging economy SMEs